2022
DOI: 10.1093/cid/ciac933
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ensitrelvir in Patients With Mild-to-Moderate Coronavirus Disease 2019: The Phase 2b Part of a Randomized, Placebo-Controlled, Phase 2/3 Study

Abstract: Background This phase 2b part of a randomized phase 2/3 study assessed the efficacy and safety of ensitrelvir for mild-to-moderate coronavirus disease 2019 (COVID-19) during the Omicron epidemic. Methods Patients were randomized (1:1:1) to orally receive ensitrelvir fumaric acid 125 mg (375 mg on day 1) or 250 mg (750 mg on day 1) or placebo once daily for 5 days. The co-primary endpoints were the change from baseline in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 25 publications
2
83
0
Order By: Relevance
“…Based on the results of the phase 2a [ 30 ] and 2b [ 31 ] studies, patients will be orally administered a once-daily dosage of ensitrelvir 125 mg, ensitrelvir 250 mg, or a matching placebo. Two types of placebo doses will be administered: placebo-B, which is identical in appearance and packaging to ensitrelvir 125 mg, and placebo-D, which is identical in appearance and packaging to ensitrelvir 250 mg. For patients assigned to the placebo group, 3 tablets each of placebo-B and placebo-D will be administered on Day 1, followed by 1 tablet each of placebo-B and placebo-D administered on Days 2 to 5.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the results of the phase 2a [ 30 ] and 2b [ 31 ] studies, patients will be orally administered a once-daily dosage of ensitrelvir 125 mg, ensitrelvir 250 mg, or a matching placebo. Two types of placebo doses will be administered: placebo-B, which is identical in appearance and packaging to ensitrelvir 125 mg, and placebo-D, which is identical in appearance and packaging to ensitrelvir 250 mg. For patients assigned to the placebo group, 3 tablets each of placebo-B and placebo-D will be administered on Day 1, followed by 1 tablet each of placebo-B and placebo-D administered on Days 2 to 5.…”
Section: Methodsmentioning
confidence: 99%
“…The phase 2a [ 30 ] and 2b [ 31 ] studies demonstrated decreased viral load with ensitrelvir treatment. In the phase 2a and 2b studies, time to improvement of COVID-19 symptoms was used for clinical assessment, similar to the assessment of influenza treatment, and a significant difference was not observed between ensitrelvir and placebo arms.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations